Facile synthesis of highly efficient bifunctional electrocatalyst by vanadium oxysulfide spheres on cobalt-cobalt sulfonitride nanosheets for oxygen and hydrogen evolution reaction - Asen, Parvin; Esfandiar, Ali (Electrochimica acta, 2021)
Synthesis of efficient, low-cost, and stable bifunctional electrocatalysts with earth-abundant resources for electrochemical water electrolysis is a challenging subject for large-scale energy conversion processes. Herein, we report a high-performance electrocatalyst based on vanadium oxysulfide/cobalt-cobalt sulfonitride (VOS/Co-CoSN) for oxygen and hydrogen evolution reaction (OER and HER). The Co-CoSN film was synthesized on a copper sheet (CS) by a facile electrodeposition method. Then, VOS was electrochemically grown onto the Co-CoSN@CS electrode at various deposition times. At the optimal deposition time (300 s), the obtained VOS-300/Co-CoSN catalyst was studied for OER and HER in alkaline and acidic media, respectively. The binder free VOS-300/Co-CoSN@CS electrode showed significant improvement in catalytic activity towards both OER (Tafel slope of 0.201 V dec−1 with overpotential of 0.34 V @100 A m−2 current density in 1.0 M KOH media) and HER (Tafel slope of 0.048 V dec−1 with overpotential of 0.18 V@100 A m−2 current density in 0.5 M H2SO4 solution). Additionally, the electrocatalyst exhibited high durability and flexibility for both OER (98% stability after 24 h at 100 A m−2) and HER (99% stability after 12 h at 0.18 V vs.RHE) in alkaline and acidic conditions, respectively. The present work not only suggests a simple and single-step strategy for the synthesis of VOS-300/Co-CoSN nanostructure but also opens up a new avenue for the development of bendable and stable bifunctional, non-noble metal electrocatalysts towards both OER and HER through water splitting procedure. [Display omitted]